EKSPERIMENTASI PENDEKATAN MEDIUM VIDEO SEBAGAI MODEL UNTUK MEMBANGUN BRANDING KOTA MELALUI LANSKAP SIMPANG LIMA SEMARANG - Nugroho, Widhi (Acintya, 2014)
Semarang city has twice the city branding efforts. Some studies suggest that both efforts have failedbecause they are not based on research and benchmarking optimally. This study will try to do theexperimental creation of city branding to Semarang with the involvement of public participation throughvisualization method with aids such as visual recording production by targeting Simpanglima regionas an area that is considered to represent the city of Semarang. Visual recording media is expected tobe a help to uncover the public memory of Semarang and their daily practices against Simpanglimaand the surrounding regions in which it is expected to appear visions that can form the key words indetermining city branding that can represent the visions of its citizens.Keywords: Visual Media, visualization, city branding and participationÂ Â Â